Potensi Antibakteri Isolat Bakteri Endofit dari Tanaman Purwoceng (Pimpinella pruatjan Molk.) Terhadap Klebsiella pneumoniae dan Salmonella typhi - Wildiani Wilson; Dewi Yuniliani (Biomedika, 2019)
This study aims to determine the isolates of purwoceng endophytic bacteria as antibacterial. Antibacterial testing was carried out using the well diffusion method. Potential endophytic bacterial isolates were first inoculated into liquid fermentation media for 52 hours and then extracted using n-hexane solvent. This crude extract is used for antibacterial testing against K. pneumoniae and S. typhi. The antibacterial activity of endophytic bacteria isolates using MHA (Mueller Hinton Agar) media with a thickness of 6 mm and a well diameter of 5 mm. The results showed that the isolates of purwoceng endophytic bacteria could not inhibit the growth of K. pneumoniae and S. typhi.